TINGKAT KETERPILIHAN KLAN POLITIK KELUARGA RATU ATUT CHOSIYAH DALAM PEMILIHAN UMUM LEGISLATIF TAHUN 2014 - Anis Fuad; Kandung Sapto Nugroho (Universitas Sultan Ageng Tirtayasa, 2017)
Banten Province which stood by the passing of Law No. 32 on October 4, 2000. Ahead of the 13th anniversary of politics in Banten province was shaken by the arrest of Tubagus Chaeri Wardana (TCW) who is also the younger brother of Ratu Atut Chosiyah by the Corruption Eradication Commission (KPK) in a hand-catching operation which then detained Ratu Atut Chosiyah in the bribery case Pemilukada Lebak Regency 2013. The implementation of legislative elections will be the first test of the shock experienced by the Family Politics Clan Ratu Atut Chosiyah. This research uses quantitative approach method. Hypothesis in this research is with the shocks on Family Clan Ratu Atut Chosiyah then the level of election of family member Atut Chosiyah in legislative election year 2014 become low. Allegations of political observers about the fall of the RAC family's political clan after the arrest of RAC and TCW by the KPK proved to have no realities. Legislative Election 2014 is true to prove to the audience that the Atut family political clan is not exhausted and still stands firmly. The people still trust their political rights to be channeled by members of the RAC Family Clans. Thus members of RAC family already have the stability and political existence in the eyes of the people of Banten. The RAC Political Clan termed by many observers as the Political Dynasty has turned out to be a self-repairing system even though some elements have problems. Have a good regeneration system where other family members can continue their political clan in Banten. Conclusions regarding the election level of members of the RAC core family clan in 2014 Legislative Election in their respective districts (1) H. Andika Hazrumy has a very high degree of election, (2) Hj. Ade Rossi Khoerunnisa has a high degree of election, (3) Andiara Aprilia Hikmat has a very high degree of election, (4) Tanto Warsono Arban has a very high degree of election, and (5) H. Aden Abdul Kholiq has a very low level of election. Therefore, all stakeholders of democracy in Banten Province should be more participative and more concerned about politics, and mobilize elements of democracy such as political parties, interest groups, academics, press, NGOs to become watchdogs of democracy in Banten, so that Atut Chosiyah political clan re-entrenched strongly in Banten does not violate the norms and rules of law applicable in Indonesia.